Culture as a Tourism Magnet A Systematic Review of the Influence of Local Traditions on Visitor Engagement in Tourism Destinations - Iswanto, Dedy; Irsyad, Ziqrurrahman (Journal of Economic Growth and Development Review, 2024)
This study explores the influence of local traditions on visitor engagement in tourism destinations, focusing on traditional elements such as music, cuisine, and crafts. Through a systematic review of relevant literature, we found that these elements not only enhance destination image but also enhance visitor satisfaction and loyalty. Cultural festivals play an important role in building emotional connections between visitors and local communities. However, there is a gap in existing research, especially regarding the interaction between traditional elements and the negative impacts of cultural integration in tourism, such as the potential erosion of cultural identity and conflicts between visitors and local communities. This study recommends the need for further studies to understand the dynamics of traditional interactions, as well as the challenges in cultural event management, to support sustainable and inclusive tourism development. These findings are expected to provide insights for destination managers and policymakers in designing more effective strategies to utilize local cultural richness.